Moderating effects of the relationship between offshore outsourcing and the export capability of firms - S. Garcilazo Lagunes; I. Danvila Del Valle; M. A. Sastre Castillo (South African Journal of Business Management, 2016)
This paper analyzes the effect of offshore outsourcing on the export performance of firms, based on the theories of international business, the resource-based view of the firm and the transaction cost theory.Outsourcing can reduce production costs and increase flexibility. It can also provide new resources and market knowledge. However, the impact of offshore outsourcing depends on the resources and capabilities of firms to manage a network of foreign suppliers, and to absorb knowledge of foreign markets. Using a database of about 1,000 manufacturing companies in Mexico in 2011, we found that offshore outsourcing increases the performance of exports. The effects are stronger in export markets from which the company also imports intermediate goods.The results also show that the size of the company, the organization of intra-firm imports and export experience moderate the effects of outsourcing in a positive way.
Keywords: 650